Volume 3: Turbo Expo 2005, Parts a and B 2005
DOI: 10.1115/gt2005-68251
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Laser Drilling Imperfection on Film Cooling Performances

Abstract: Film cooling is studied on a jet in a cross-flow. The influence of a hole production imperfection on the jet-cross flow interaction is investigated experimentally by means of particle image velocimetry and liquid crystal thermography. To simulate the imperfection a half torus was placed inside the hole. The experiments were conducted with and without the production imperfection and the velocity ratio was varied. If the imperfection is absent, vortices are generated by means of the Kelvin-Helmholtz instability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…These structures affect the film cooling process (see Jovanović et al, 2005). The largest are the lee, windward vortices and a counter rotating pair known also as kidney vortices.…”
Section: Integral Curvesmentioning
confidence: 98%
See 2 more Smart Citations
“…These structures affect the film cooling process (see Jovanović et al, 2005). The largest are the lee, windward vortices and a counter rotating pair known also as kidney vortices.…”
Section: Integral Curvesmentioning
confidence: 98%
“…The experiments were conducted in a water channel at the Technische Universiteit Eindhoven (Eindhoven University of Technology) (for details see Jovanović et al, 2005). A plexiglas flat plate (2400 Â 565 mm) is placed in the test section.…”
Section: Experimental Set-upmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies have shown the detrimental effects on adiabatic effectiveness of in-hole blockages in cylindrical film cooling holes. Jovanovic et al [3] found significant changes in the flowfield of a cylindrical hole blocked with a half torus shaped blockage, which is commonly found in the melt ejection during laser drilling. Large decreases in film cooling effectiveness were also found, with the decreases being larger at low velocity ratios.…”
Section: Relevant Past Studiesmentioning
confidence: 99%
“…Imperfections may also be produced during manufacturing of the holes and refurbishing of the holes after long hours of flight. It is known that imperfections in a hole may reach even 25% of hole diameter [3].…”
Section: Introductionmentioning
confidence: 99%